2018
DOI: 10.2298/fil1806173e
|View full text |Cite
|
Sign up to set email alerts
|

Extended Dai-Yuan conjugate gradient strategy for large-scale unconstrained optimization with applications to compressive sensing

Abstract: We present a new spectral conjugate gradient method based on the Dai-Yuan strategy to solve large-scale unconstrained optimization problems with applications to compressive sensing. In our method, the numerator of conjugate gradient parameter is a convex combination from the maximum gradient norm value in some preceding iterates and the current gradient norm value. This combination will try to produce the larger step-size far away from the optimizer and the smaller step-size close to it. In addition, the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Due to simpler structure and low memory requirements of Dai-Liao conjugate gradient methods; Yao, et al (2019) proposed some three-term Dai-Liao CG algorithms that possess efficient conjugate gradient structures. Esmaeili, et al (2018) suggested a new CG scheme to solve problems emerged from astronomical imaging, file restoration, image video coding and other applications. Similarly, Guo & Wan (2019) developed CG algorithm for sparse engineering signal problem.…”
Section: Extended Conjugacy Condition Of Dai and Liao Cg Methods (Eccdl)mentioning
confidence: 99%
“…Due to simpler structure and low memory requirements of Dai-Liao conjugate gradient methods; Yao, et al (2019) proposed some three-term Dai-Liao CG algorithms that possess efficient conjugate gradient structures. Esmaeili, et al (2018) suggested a new CG scheme to solve problems emerged from astronomical imaging, file restoration, image video coding and other applications. Similarly, Guo & Wan (2019) developed CG algorithm for sparse engineering signal problem.…”
Section: Extended Conjugacy Condition Of Dai and Liao Cg Methods (Eccdl)mentioning
confidence: 99%